THE MINERALOGICAL COMPOSITION OF THRACE ZEOLITIC ROCKS AND THEIR POTENTIAL USE AS FEED ADDITIVES AND NUTRITION SUPPLEMENTS - Filippidis, A.; Kantiranis, N.; Tsirambides, A. (Bulletin of the Geological Society of Greece, 2016)
Thirty two (32) locations of zeolitic rocks from Thrace (29 from Evros prefecture and 3 from Rhodope prefecture) were investigated for their mineralogical composition by X-Ray Diffraction (XRD) method. According to EU Regulation No 651/2013, clinoptilolite of sedimentary origin (zeolitic tuffs) with ≥80 wt% clinoptilolite, ≤20 wt% clay minerals, free of fibres and quartz, can be used as feed additive for all animal species. The zeolitic rocks of Thrace on average contain, 23-89 wt% HEUtype zeolite (clinoptilolite-heulandite), 8-45 wt% mordenite (ten locations), 24 wt% analcime (one location), 1-11 wt% mica, 1 11 wt% clay minerals, 3-37 wt% quartz, 2-29 wt% cristobalite, 3-34 wt% feldspars and 0-22 wt% amorphous materials. Only one location contains 89 wt% HEU-type zeolite (clinoptilolite-heulandite), 2 wt% clay minerals, is free of fibres, but unfortunately it contains 3 wt% quartz and 2 wt% cristobalite. Considering the mineralogical composition, the zeolitic rocks of Thrace do not meet the requirements of the EU Regulation No 651/2013, and thus cannot be used as feed additives for all animal species and consequently as nutrition supplements, since the zeolitic rocks in all locations, contain on average 3-37 wt% quartz, 2-29 wt% cristobalite, 8-45 wt% mordenite (fibrous zeolite) in 10 locations, 24-65 wt% zeolites (HEU-type ± mordenite ± analcime) in 28 locations, 74 wt% HEUtype zeolite in 2 locations and 77 wt% HEU-type zeolite in 1 location.